AERODYNAMIC AND STRUCTURAL ANALYSIS OF COMPOSITE BLENDED WINGLETS FOR ALUDRA-EE UAV (Journal of Transport System Engineering, 2026)
Unmanned Aerial Vehicles (UAVs) commonly experience induced drag generated by wingtip vortices, which negatively affects aerodynamic efficiency and endurance. This study investigates the aerodynamic and structural performance of blended composite winglets for the ALUDRA-EE UAV using Computational Fluid Dynamics (CFD) and finite element analysis. Three winglet cant angle configurations (0°, 45°, and 60°) based on the RONCZ 1046 airfoil were evaluated using ANSYS Fluent to analyse lift, drag, lift-to-drag ratio, and vortex intensity. The aerodynamic results showed that the 60° blended winglet produced the best overall performance, achieving the highest lift-to-drag ratio of 22.23 and the lowest vortex intensity among all configurations. The optimized winglet configuration improved UAV range and endurance by approximately 26.14% and 41.7%, respectively. Structural analyses were subsequently conducted using Abaqus to evaluate hollow and solid composite winglet designs with different composite material configurations and ply orientations. The solid winglet constructed using standard carbon fibre fabric demonstrated the lowest displacement and failure indices while maintaining acceptable structural integrity under aerodynamic loading. The findings indicate that the proposed 60° composite blended winglet can significantly enhance the aerodynamic efficiency and structural performance of the ALUDRA-EE UAV.
Keywords: Aerodynamics; CFD; blended winglet; cant angle; composite